Associations of multiple visual rating scales based on structural magnetic resonance imaging with disease severity and cerebrospinal fluid biomarkers in patients with Alzheimer’s disease - Wan, Mei-dan; Liu, Hui; Liu, Xi-xi; Zhang, Wei-wei; Xiao, Xue-wen; Zhang, Si-zhe; Jiang, Ya-ling; Zhou, Hui; Liao, Xin-xin; Zhou, Ya-fang; Tang, Bei-sha; Wang, Jun-Ling; et al. (Frontiers in Aging Neuroscience, 2022)
The relationships between multiple visual rating scales based on structural magnetic resonance imaging (sMRI) with disease severity and cerebrospinal fluid (CSF) biomarkers in patients with Alzheimer's disease (AD) were ambiguous. In this study, a total of 438 patients with clinically diagnosed AD were recruited. All participants underwent brain sMRI scan, and medial temporal lobe atrophy (MTA), posterior atrophy (PA), global cerebral atrophy-frontal sub-scale (GCA-F) and Fazekas rating scores were visually evaluated. Meanwhile, the disease severity was assessed by neuropsychological tests for Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA) and Clinical Dementia Rating (CDR). Among them, 95 patients were tested for CSF core biomarkers, including Aβ1-42, Aβ1-40, Aβ1-42/1-40, p-tau, t-tau. As a result, the GCA-F, and Fazekas scales showed positively significant correlations with onset age (r = 0.181, p < 0.001; r = 0.411, p < 0.001; respectively). Patients with late-onset AD (LOAD) showed higher GCA-F and Fazekas scores (p < 0.001, p < 0.001). With regard to disease duration, the MTA and GCA-F was positively correlated (r = 0.137, p < 0.05; r = 0.106, p < 0.05; respectively). In terms of the disease severity, a positively significant association emerged between disease severity with MTA, PA GCA-F, and Fazekas (p < 0.001, p < 0.001, p < 0.001, p < 0.05 respectively). Moreover, after adjusting for age, gender and APOE alleles, the MTA scale contributed to moderate-severe AD in statistical significance independently by multivariate logistic regression analysis (p < 0.05). The model combining visual rating scales, age, gender, and APOE alleles, showed the best performance for the prediction of moderate-severe AD significantly (AUC = 0.712, sensitivity = 51.5%, specificity = 84.6%). Additionally, we observed that the MTA scores and Fazekas scores were associated with a lower concentration of Aβ1-42 (p < 0.031, p < 0.022, respectively). In summary, we systematically analyzed the benefits of multiple visual rating scales in predicting clinical status with AD. The visual rating scales combining with age, gender and APOE alleles showed the best performance in predicting the severity of AD. And MRI biomarkers in combination with CSF biomarkers can be used in clinical practice.